1992
DOI: 10.1111/j.1439-0531.1992.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Remove Bovine Diarrhea Virus (BVDV) from Bull Semen by Swim up and other Separatory Sperm Techniques Associated with in vitro Fertilization

Abstract: Contents:Semen samples, collected from bulls pesistently ir5fected with bovine viral diarrhea virus (BVDV) and containing BVDV (titer I @ -I @TCID,dml), were subjected to sperm separation procedures (washing, swim up, Percoll gradient, glass wool filtration, glass beads filtration) that are commonly usedprior to in vitro fertilization ( N F ) to determine $these procedures would yield spermatozoa free from BVDV. The final sperm pellets from frozen and fresh ejaculates were tested for the presence of BVDV by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 12 publications
4
6
0
Order By: Relevance
“…Extended isolation (quarantine) in association with routine periodic monitoring from presence of detectable virus in semen might be advisable for some valuable bulls diagnosed with persistent testicular infection. Bovine viral diarrhea virus in semen may be associated with sperm and cannot be removed by centrifugation through a percoll gradient, swim-up techniques, glass wool filtration or glass bead filtration (Bielanski et al, 1992).…”
Section: Viral Pathogensmentioning
confidence: 99%
“…Extended isolation (quarantine) in association with routine periodic monitoring from presence of detectable virus in semen might be advisable for some valuable bulls diagnosed with persistent testicular infection. Bovine viral diarrhea virus in semen may be associated with sperm and cannot be removed by centrifugation through a percoll gradient, swim-up techniques, glass wool filtration or glass bead filtration (Bielanski et al, 1992).…”
Section: Viral Pathogensmentioning
confidence: 99%
“…Bovine viral diarrhoea virus was isolated from in vitro-produced embryos after use of BVD virus-infected semen (Bielanski, 1995). It has been reported that after the use of persistently intended bull semen, cleavage rates and development to the blastocyst stage were not significantly reduced in IVF (Bielanski et al, 1992). In contrast, Guerin and colleagues (1992) demonstrated that fertilization and cleavage were significantly decreased when semen from persistently infected bulls was used for IVF.…”
Section: Discussionmentioning
confidence: 85%
“…Even after freezing, many microorganisms, either in pure cultures or associated with germplasm, are not completely removed from sperm cryopreserved using conventional methods, can survive to storage in liquid nitrogen and may be subsequently isolated from thawed bull semen (Gonzalez‐Marin et al, ). Therefore, although AI with frozen sperm can reduce potential contamination of cows, their genital tract may still be contaminated with agents transmitted by bull semen (Bielanski, Dubuc, & Hare, ; Nash, Hanson, & Coats, ; Visser et al, ), which implies that oocytes and embryos can be infected (Bielanski & Vajta, ).…”
Section: Discussionmentioning
confidence: 99%